Ensino de leitura para uma criança com autismo baseado em jogos de mesa - Zagato, Bruno (Universidade Federal de São Carlos, 2024)
Reading proficiency is an important factor in academic success, as it allows students to understand material, obtain information and be active participants in other school activities. Reading, in certain cases and situations, can be a difficult skill to master for students with Autism Spectrum Disorder. Due to the difference in sensory framework, information processing and language skills, students with ASD can suffer major deficits in the development of reading skills. The aim of this study was to verify the effect of responding in board games on the emergence or improvement of reading performance in children with ASD. The procedure used was based on identity pairing attempts between pictures and words, arbitrary pairing between pictures and words in four board games (memory, bingo, connect words and word search) and the use of differential consequences. The participants were children diagnosed with ASD. The design consisted of a baseline reading test, application of the games in a teaching situation and a reading post-test and follow-up. Thus, the research had one participant and the results indicated the emergence of reading twelve words and the achievement of learning performance in all the games.
Reading teaching for a child with autism based on board games
Keywords: Educação especial; Transtorno do Espectro do Autismo; Jogos; Repertórios; Acadêmicos; Equivalência de estímulos; Special education; Autism Spectrum Disorder; Games; Reading; Stimulus equivalence; CIENCIAS HUMANAS::EDUCACAO